How to Solve Polynomials: 13 Steps (with Pictures)

A polynomial is an expression created to add and subtract terms. A term can be made up of constants, coefficients, and variables. When solving polynomials, we usually try to find the values of each x, y = 0. Polynomials of lower degrees will have zero, one, or two real solutions, depending on whether they are linear polynomials or quadratic polynomials. These types of polynomials can be easily solved using basic algebra and factoring methods. If you want to know how to solve polynomials of higher degree, read the article How to solve polynomials of higher degrees.

Steps

Method 1 of 2: Solve a Linear Polynomial

Step 1. Determine if you have a linear polynomial

A linear polynomial is a polynomial of the first degree. This means that no variable will have an exponent higher than one. Since this is a first degree polynomial, it will have exactly one real root or solution.

• For example, 5x + 2 { displaystyle 5x + 2}

es un polinomio lineal, porque la variable x{displaystyle x}

no tiene exponente (lo que es igual a un exponente de 1).

Step 2. Set the equation equal to zero

This is a necessary step to solve all the polynomials.

• For example, 5x + 2 = 0 { displaystyle 5x + 2 = 0}

Step 3. Solve for the variable in the term

To do this, add or subtract the constant from both sides of the equation. A constant is a term without a variable.

• For example, to solve for the variable x { displaystyle x}

en 5x+2=0{displaystyle 5x+2=0}

, debes restar 2{displaystyle 2}

de ambos lados de la ecuación:

5x+2=0{displaystyle 5x+2=0}

5x+2−2=0−2{displaystyle 5x+2-2=0-2}

5x=−2{displaystyle 5x=-2}

Step 4. Solve for the variable

Generally, you will need to divide each side of the equation by the coefficient. This will give you the root or solution to your polynomial.

• For example, to solve for x { displaystyle x}

in 5x=−2{displaystyle 5x=-2}

:

5x=−2{displaystyle 5x=-2}

5x5=−25{displaystyle {frac {5x}{5}}={frac {-2}{5}}}

x=−25{displaystyle x={frac {-2}{5}}}

Por lo tanto, es la solución a 5x+2{displaystyle 5x+2}

is x=−25{displaystyle x={frac {-2}{5}}}

Método 2 de 2: Resolver un polinomio cuadrático

Step 1. Determine if you have a quadratic polynomial

A quadratic polynomial is a polynomial of the second degree. This means that no variable will have an exponent higher than two. Since this is a second degree polynomial, it will have two real roots or solutions.

• For example, x2 + 8x − 20 { displaystyle x ^ {2} + 8x-20}

es un polinomio cuadrático, porque la variable x{displaystyle x}

tiene un exponente de 2{displaystyle 2}

Step 2. Make sure the polynomial is written in order of degree

This means that the term with the exponent of 2 { displaystyle 2}

se enuncia primero, seguido del término de primer grado, seguido de la constante.

• Por ejemplo, debes reescribir 8x+x2−20{displaystyle 8x+x^{2}-20}
• como x2+8x−20{displaystyle x^{2}+8x-20}

Step 3. Set the equation equal to zero

This is a necessary step to solve all the polynomials.

• For example, x2 + 8x − 20 = 0 { displaystyle x ^ {2} + 8x-20 = 0}

Step 4. Rewrite the expression as a four-term expression

To do this, separate the first degree term (the term x { displaystyle x}

). Aquí deberás buscar dos números cuya suma sea igual al coeficiente de primer grado y cuyo producto sea igual a la constante.

• Por ejemplo, para el polinomio cuadrático x2+8x−20=0{displaystyle x^{2}+8x-20=0}
• , necesitas encontrar dos números (a{displaystyle a}

y b{displaystyle b}

), donde a+b=8{displaystyle a+b=8}

, y a⋅b=−20{displaystyle a\cdot b=-20}

• Como tienes −20{displaystyle -20}
• , sabemos que uno de los números será negativo.

• Deberás ver que 10+(−2)=8{displaystyle 10+(-2)=8}
• y 10⋅(−2)=−20{displaystyle 10\cdot (-2)=-20}

. En consecuencia, debes separar 8x{displaystyle 8x}

dentro de 10x−2x{displaystyle 10x-2x}

y reescribir el polinomio cuadrático: x2+10x−2x−20=0{displaystyle x^{2}+10x-2x-20=0}

Step 5. Factor by grouping

To do this, factor a term common to the first two terms in the polynomial.

• For example, the first two terms in the polynomial x2 + 10x − 2x − 20 = 0 { displaystyle x ^ {2} + 10x-2x-20 = 0}

son x2+10x{displaystyle x^{2}+10x}

. Un término común a los dos es x{displaystyle x}

. Así, el grupo factorizado es x(x+10){displaystyle x(x+10)}

Step 6. Factor the second group

To do this, factor a common term to the second two terms in the polynomial.

• For example, the two second terms in the polynomial x2 + 10x − 2x − 20 = 0 { displaystyle x ^ {2} + 10x-2x-20 = 0}

son −2x−20{displaystyle -2x-20}

. Un término común a los dos es −2{displaystyle -2}

. Entonces, el grupo factorizado es −2(x+10){displaystyle -2(x+10)}

Step 7. Rewrite the polynomial as two binomials

A binomial is an expression of two terms. You already have a binomial, which is the expression in parentheses for each group. This expression must be the same for each group. The second binomial is created by combining the two terms that were factored from each group.

• For example, after factoring by grouping, x2 + 10x − 2x − 20 = 0 { displaystyle x ^ {2} + 10x-2x-20 = 0}

esto se convierte en x(x+10)−2(x+10)=0{displaystyle x(x+10)-2(x+10)=0}

• El primer binomio es (x+10){displaystyle (x+10)}
• El segundo binomio es (x−2){displaystyle (x-2)}
• Por lo tanto, el polinomio cuadrático original x2+8x−20=0{displaystyle x^{2}+8x-20=0}
• se puede escribir como la expresión factorizada (x+10)(x−2)=0{displaystyle (x+10)(x-2)=0}

Step 8. Find the first root or solution

To do this, solve for x { displaystyle x}

en el primer binomio.

• Por ejemplo, para encontrar la primera raíz para (x+10)(x−2)=0{displaystyle (x+10)(x-2)=0}
• , primero debes llevar la expresión inicial del binomio a 0{displaystyle 0}

y resolver x{displaystyle x}

. En consecuencia:

x+10=0{displaystyle x+10=0}

x+10−10=0−10{displaystyle x+10-10=0-10}

x=−10{displaystyle x=-10}

Así que, la primera raíz del polinomio cuadrático x2+8x−20=0{displaystyle x^{2}+8x-20=0}

es −10{displaystyle -10}

Step 9. Find the second root or solution

To do this, solve for x { displaystyle x}

en el segundo binomio.

• por ejemplo, para encontrar la segunda raíz para (x+10)(x−2)=0{displaystyle (x+10)(x-2)=0}
• , debes llevar la segunda expresión del binomio a 0{displaystyle 0}

y resolver x{displaystyle x}

x−2=0{displaystyle x-2=0}

x−2+2=0+2{displaystyle x-2+2=0+2}

x=2{displaystyle x=2}

de esta manera, la segunda raíz del polinomio cuadrático x2+8x−20=0{displaystyle x^{2}+8x-20=0}

es 2{displaystyle 2}

consejos

• no te preocupes si obtienes diferentes variables, como t, o si ves una ecuación llevada a f(x) en vez de 0. si la pregunta requiere raíces, ceros o factores, simplemente trátala como cualquier otro problema.
• recuerda el orden de las operaciones mientras trabajas. primero trabaja resuelve el paréntesis, luego haz la multiplicación y división, y finalmente suma y resta.